Wrist Wearable Health Band for COVID-19 Testing - K., Kanishkar; V., Raghul; Sai, Nithish; A., Stanley Raj (Journal of Medical Informatics and Decision Making, 2020)
Testing people for COVID-19 in a country like India with a huge population is a near impossible task therefore the government is using body temperature as a testing parameter to cover the whole population. Infrared thermometers are used to find the temperature because it is a cheaper and faster way. This testing rate can be done even faster, without the need of manpower and with far more accuracy using smart watches and bands. These wrist-wearables are mostly used for fitness purposes which have more measuring equipment that is used for preliminary testing done for COVID. This equipment’s are in the form of electric sensors which are small enough to be used in wearables. So we can get even more insight and accuracy compared to the standard method. In this study an application is created to use an array of sensors (Pulse sensor, Pulse oximeter, Accelerometer and temperature sensor) are being used in these wearables to find the chance, that a person is affected due to COVID-19 and the information can be seen real time in mobile phone through the application. All the information can be sent to the health organization’s if required.
Keywords: Wrist-wearables. COV1D-19. Pulse sensor. Pulse Oximeter. Accelerometer.